2009
DOI: 10.1038/aps.2009.31
|View full text |Cite
|
Sign up to set email alerts
|

Genipin inhibits endothelial exocytosis via nitric oxide in cultured human umbilical vein endothelial cells

Abstract: Aim: Exocytosis of endothelial Weibel-Palade bodies, which contain von Willebrand factor (VWF), P-selectin and other modulators, plays an important role in both inflammation and thrombosis. The present study investigates whether genipin, an aglycon of geniposide, inhibits endothelial exocytosis. Methods: Human umbilical vein endothelial cells (HUVECs) were isolated from umbilical cords and cultured. The concentration of VWF in cell supernatants was measured using an ELISA Kit. P-selectin translocation on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…We also found that genipin, the aglycone of geniposide, inhibits endothelial exocytosis in HUVECs by stimulating nitric oxide production [15] . However, whether geniposide prevents high glucose-induced vascular injury was not investigated.…”
Section: Introductionmentioning
confidence: 68%
“…We also found that genipin, the aglycone of geniposide, inhibits endothelial exocytosis in HUVECs by stimulating nitric oxide production [15] . However, whether geniposide prevents high glucose-induced vascular injury was not investigated.…”
Section: Introductionmentioning
confidence: 68%
“…Genipin exerts anti-inflammatory, anti-angiogenic, antiproliferative and hepatoprotective activities in several cell lines including murine macrophage cells, human umbilical vein endothelial cells, human prostate cancer cells, and human hepatocarcinoma cells (2)(3)(4)(5). Genipin has been shown to inhibit growth of human leukemia and prostate cancer cells (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/aps Feng Q et al Acta Pharmacologica Sinica npg cells (HUVECs), suppresses vascular and endothelial cell infl ammatory activation, and may target acute infl ammatory events [12] . Notably, genipin has been shown to induce dosedependent apoptosis in FaO rat hepatoma cells, human hepatocarcinoma Hep3B cells [13] and PC3 human prostate cancer cells [14] .…”
mentioning
confidence: 99%